Mechanism underlying polyvalent IgG-induced regulatory T cell activation and its clinical application: Anti-idiotypic regulatory T cell theory for immune tolerance - Victor, Jefferson Russo; Nahm, Dong-Ho (Frontiers in Immunology, 2023)
The regulatory T (Treg) cells constitute a functionally defined subpopulation of T cells that modulate the immune system and maintain immune tolerance through suppression of the development of autoimmune responses to self-antigens and allergic reactions to external antigens. Reduction in the number or function of Treg cells has been suggested as a key immune abnormality underlying the development of autoimmune and allergic diseases. In vitro studies have demonstrated that purified polyvalent immunoglobulin G (IgG) from multiple healthy blood donors can exert immunomodulatory effects on Treg cells. Incubation of polyvalent human IgG with purified CD4+CD25high T cells increased the intracellular expression of interleukin (IL)-10. Intravenous administration of polyvalent human IgG induced a significant expansion of CD4+ Foxp3+ Treg cells in the peripheral blood of patients with autoimmune diseases. In human clinical trials, intramuscular administration of autologous total IgG significantly increased the percentage of IL-10-producing CD4+ Treg cells in the peripheral blood of healthy subjects and provided significant clinical improvements in patients with atopic dermatitis. These results suggest a clinical usefulness of polyvalent IgG-induced activation of Treg cells in human subjects. This review proposes a new immune tolerance mechanism by integrating the “idiotypic network theory” and “Treg cell theory” into an “anti-idiotypic Treg cell theory.” Based on this hypothesis, an “active anti-idiotypic therapy” for allergic and autoimmune diseases using autologous polyvalent IgG (as immunizing antigens) is suggested as follows: (1) Intramuscular or subcutaneous administration of autologous polyvalent IgG produces numerous immunogenic peptides derived from idiotypes of autologous IgG through processing of dendritic cells, and these peptides activate anti-idiotypic Treg cells in the same subject. (2) Activated anti-idiotypic Treg cells secrete IL-10 and suppress Th2 cell response to allergens and autoimmune T cell response to self-antigens. (3) These events can induce a long-term clinical improvements in patients with allergic and autoimmune diseases. Further studies are needed to evaluate the detailed molecular mechanism underlying polyvalent IgG-induced Treg cell activation and the clinical usefulness of this immunomodulatory therapy for autoimmune and allergic diseases.